Methylene-tetrahydrofolate reductase contributes to allergic airway disease. - Kenneth R Eyring; Brent S Pedersen; Kenneth N Maclean; Sally P Stabler; Ivana V Yang; David A Schwartz (PLoS ONE, 2018)
Environmental exposures strongly influence the development and progression of asthma. We have previously demonstrated that mice exposed to a diet enriched with methyl donors during vulnerable periods of fetal development can enhance the heritable risk of allergic airway disease through epigenetic changes. There is conflicting evidence on the role of folate (one of the primary methyl donors) in modifying allergic airway disease.We hypothesized that blocking folate metabolism through the loss of methylene-tetrahydrofolate reductase (Mthfr) activity would reduce the allergic airway disease phenotype through epigenetic mechanisms.Allergic airway disease was induced in C57BL/6 and C57BL/6Mthfr-/- mice through house dust mite (HDM) exposure. Airway inflammation and airway hyperresponsiveness (AHR) were measured between the two groups. Gene expression and methylation profiles were generated for whole lung tissue. Disease and molecular outcomes were evaluated in C57BL/6 and C57BL/6Mthfr-/- mice supplemented with betaine.Loss of Mthfr alters single carbon metabolite levels in the lung and serum including elevated homocysteine and cystathionine and reduced methionine. HDM-treated C57BL/6Mthfr-/- mice demonstrated significantly less airway hyperreactivity (AHR) compared to HDM-treated C57BL/6 mice. Furthermore, HDM-treated C57BL/6Mthfr-/- mice compared to HDM-treated C57BL/6 mice have reduced whole lung lavage (WLL) cellularity, eosinophilia, and Il-4/Il-5 cytokine concentrations. Betaine supplementation reversed parts of the HDM-induced allergic airway disease that are modified by Mthfr loss. 737 genes are differentially expressed and 146 regions are differentially methylated in lung tissue from HDM-treated C57BL/6Mthfr-/- mice and HDM-treated C57BL/6 mice. Additionally, analysis of methylation/expression relationships identified 503 significant correlations.Collectively, these findings indicate that the loss of folate as a methyl donor is a modifier of allergic airway disease, and that epigenetic and expression changes correlate with this modification. Further investigation into the mechanisms that drive this observation is warranted.